BPC-157 and GHK-Cu in Wound Healing and Tissue Repair: A Review of Clinical Efficacy and Safety - Wojcieszuk, Olaf; Starczewski, Łukasz; Babik, Adrianna; Kamińska, Kamila; Będkowska-Kuśmierek, Matylda; Złotnik, Anna; Krzysztofik, Kinga; Klamka, Antoni; Kawalec, Paulina; Bronikowski, Kamil (Quality in Sport, 2026)
Background: BPC-157 and GHK-Cu are synthetic peptides with potential in tissue repair, influencing molecular mechanisms in healing, angiogenesis and inflammation. Objective: This review synthesizes preclinical and clinical research on BPC-157 and GHK-Cu efficacy and safety in wound healing and tissue repair, examining mechanistic pathways and translational potential in clinical and sports medicine. Methods: Literature searches of PubMed, Embase and Cochrane Library included studies on wound healing, tissue regeneration, safety and clinical uses of BPC-157 and GHK-Cu without publication date restrictions. Results: Preclinical studies show BPC-157 promotes skin, tendon, muscle and bone healing via specific signaling pathways and growth factor upregulation. GHK-Cu enhances collagen/elastin synthesis, angiogenesis and fibroblast migration. Limited human trials evaluated BPC-157 for knee pain and IV safety, while GHK-Cu showed promise in skin quality trials. Both appear safe but lack comprehensive RCTs. Conclusion: BPC-157 and GHK-Cu show therapeutic potential in wound healing, though evidence is largely preclinical. Extensive human trials are needed to establish clinical efficacy. This review provides groundwork for future research and highlights safety for sports medicine practitioners.